Antioxidant Activities and Phenolic Compositions of Wheat Germ as Affected by the Roasting Process. (21st July 2015) - Zou, Yanping; Yang, Miao; Zhang, Ge; He, Hui; Yang, Tiankui
Abstract: Wheat germ is a good source for wheat germ oil, and it is a by‐product with highly concentrated nutrients from the wheat flour‐milling industries. In the present study, raw wheat germ was firstly heat‐treated at 180 °C for 20 min in a fluidized bed dryer, and further roasted at 180 °C for different periods of time. Roasting influence on total phenolic content (TPC), antioxidant activities, and phenolic compositions of wheat germ were evaluated. The roasting process significantly increased the TPC and antioxidant activities including free radical scavenging against DPPH and ABTS radicals, FRAP, and ORAC. In particular, the wheat germ roasted at 180 °C for 20 min showed higher antioxidant activity than those roasted at 180 °C for 5 and 10 min. Three major phenolic acids, namely, ferulic, chlorogenic, and caffeic acid, and four main flavonoids, namely, schaftoside and its isomers or adduct of sinapic acid were identified by HPLC. In general, the content of individual phenolic compounds decreased with prolongation of the roasting time except for ferulic acid. The results suggest that the antioxidant activities of wheat germ can be enhanced by roasting, and the enhancement effect might be partially attributed to the formation of Maillard reaction products (MRP).